Distribution of Sea Surface Temperature in Dodinga Bay Its Relationship with Small Pelagic Fish Catch - Malik, Fikri R.; Darmawaty, Darmawaty (Agrikan Jurnal Agribisnis Perikanan, 2021)
The research was carried out using experimental fishing methods with data analysis in the form of geographic information system and non-linear regression analisys , with the aim of studying the distribution of sea surface temperature in relation to the catch of small pelagic fish in the waters of Dodinga Bay. The results showed that the distribution of the average sea surface temperature in April-July 2021 in the Dodinga Bay waters was quite volatile and was in the range of 28.62 oC - 29.48 oC, with a total catch of 3,979.85 kg, where this variable has a close relationship with the equation non-linear regression y = 0.0054x2 - 0.5329x + 41.502 and the correlation coefficient (r) is 0.786. The results also showed that the highest catch value was in the sea surface temperature range between 28.0 - 29.9 oC. The results of this study are preliminary information so that in an effort to manage small pelagic fish to the optimum level, field validation is necessary.